Hubungan Pengetahuan Dan Pendidikan Ibu Dengan Pemberian ASI Perah Pada Ibu Bekerja di Wilayah Kerja Puskesmas Karya Wanita - Dewi Sartika Siagian; Siti Qomariah; Serly Mustika (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2026)
The World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) report that global exclusive breastfeeding coverage stands at 48%, below the 50% target for 2025. In Indonesia, the 2024 achievement rate was 74.73%, but at the Karya Wanita Health Center in Pekanbaru City, it was only 27.7%. This low rate is influenced by factors such as mothers' knowledge and education. For working mothers, expressed breast milk feeding is a solution to ensure infants continue to receive breast milk. This study aims to determine the relationship between mothers' knowledge and education levels and expressed breast milk feeding among working mothers in the service area of the Karya Wanita Health Center in Pekanbaru City. This study is a quantitative study with a cross-sectional design. The sample consisted of 43 working mothers with infants aged 0–12 months, selected using accidental sampling. Data were collected through questionnaires and analyzed univariately and bivariate using Fisher's exact test. The majority of respondents had good knowledge (67.4%) and higher education (46.5%). A total of 67.4% provided expressed breast milk. There was a significant association between knowledge and the provision of expressed breast milk (p = 0.000), as well as between education and the provision of expressed breast milk (p = 0.000). There is a significant relationship between mothers' knowledge and education levels and the provision of expressed breast milk among working mothers. Educational efforts and support from healthcare workers are needed to ensure that working mothers have the knowledge and motivation to provide expressed breast milk optimally.